PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN PADA PT. JALUR NUGRAHA EKAKURIR (JNE) PEKANBARU - Dewi Sartika Agustiar Sihombing; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this research is to determine the effect of service quality and corporate image of consumer satisfaction at PT. Jalur Nugraha Ekakurir (JNE) Pekanbaru. Service quality and corporate image as an independent variable () while consumer satisfaction as the dependent variable (Y). The research method used is quantitative descriptive analysis. Data obtained from secondary data by the company and primary data through questionnaires measured with a Likert scale and then processed with SPSS version 22. The sample of this study were 98 respondents from the population calculated using the Slovin formula. Data analysis techniques in this study use simple linear regression analysis and multiple linear regression analysis.From the results of the research conducted showed that service quality has an effect on consumer satisfaction with a value of t arithmetic> t table (13, 109> 1.6608) and significance (0,000 <0.05). The corporate image has an effect on consumer satisfaction with the value of t count> t table (14, 804> 1.6608) and significance (0,000 <0.05). Service quality and corporate image influence consumer satisfaction with a calculated F value> F table (137.744> 3.09) and significance (0.000 <0.05). It can be concluded that service quality and corporate image have a positive and significant impact on consumer satisfaction at PT. Jalur Nugraha Ekakurir (JNE) Pekanbaru. Keywords: Service Quality, Coorporate Image, Consumer Satisfaction